Holocaust Memory and Public History : Examining Holocaust Museums from 1947-2001 - Lahti, Hannah M.; Sanisio, Teresa M.; Oberly, James W. (My University, 2019)
Holocaust museums and memorials are central features to Holocaust memory and education. The phrase “Never Again” continues to be a theme in Holocaust memory, which has led to support for Holocaust education. The Auschwitz-Birkenau Memorial and Museum, Yad Vashem World Holocaust Remembrance Center, United States Holocaust Memorial Museum (USHMM), and Jewish Museum Berlin (JMB) were established in different geographic locations and at different times since 1945. These museums are influenced by different factors, such as nationalism, religion, politics, and culture. Each museum teaches about the Holocaust similarly, but their unique exhibits are designed to evoke emotion and memory in different ways. Public history allows historical content to be shared outside of a standard academic setting, encouraging the public to learn history outside of a classroom. For this reason, Holocaust museums have become some of the most important facilitators of Holocaust education. This study aims to examine the ways in which historical memory is reflected in four different Holocaust museums. Contextualizing and comparing these museums and their unique exhibits will further the understanding of Holocaust memory and representation over time and in different locations.
Color poster with text and photographs.
Keywords: Holocaust museums; Holocaust, Jewish (1939-1945); History education; Posters